2007
DOI: 10.1021/jp0747151
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Photocatalysts Based on Homogeneous and Heterogenized Tin Porphyrins

Abstract: Visible light photocatalysis using water-soluble tin porphyrin (s-SnP, [Sn(OH 2 ) 2 (TPy H P)](NO 3 ) 6 ) and waterinsoluble tin porphyrin Sn(OH) 2 (TPP) (ins-SnP) immobilized on SiO 2 (hetero-SnP) was investigated. The visible light photocatalytic activities of s-SnP and hetero-SnP were demonstrated successfully for the degradation of 4-chlorophenol (4-CP) and acid orange 7 (AO7) in water. The visible light activity of hetero-SnP increased with the ins-SnP loading and was saturated above 77 mg/g-SiO 2 , which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 28 publications
0
54
0
Order By: Relevance
“…Crude hexakis adduct was isolated using a liquid chromatography, hydrolyzed and subsequently converted into its hydrochloride salt, and then purified by dialysis and dried in vacuum. trans-dihydroxo [5,10,15,20-tetraphenylporphyrinato]tin(IV), Sn(OH) 2 (TPP) and trans-dihydroxo [5,10,15,20-tetrakis-(4-pyridyl) porphyrinato]tin(IV), Sn(OH) 2 (TPyP) were prepared using the previously-reported method [31]. The former one (i.e., ins-SnP), which exhibits extremely low aqueous solubility, was immobilized on silica support to form tin porphyrin-based heterogeneous sensitizer, SnP/silica.…”
Section: Preparation Of Sensitizers As Water-soluble and Immobilized mentioning
confidence: 99%
See 1 more Smart Citation
“…Crude hexakis adduct was isolated using a liquid chromatography, hydrolyzed and subsequently converted into its hydrochloride salt, and then purified by dialysis and dried in vacuum. trans-dihydroxo [5,10,15,20-tetraphenylporphyrinato]tin(IV), Sn(OH) 2 (TPP) and trans-dihydroxo [5,10,15,20-tetrakis-(4-pyridyl) porphyrinato]tin(IV), Sn(OH) 2 (TPyP) were prepared using the previously-reported method [31]. The former one (i.e., ins-SnP), which exhibits extremely low aqueous solubility, was immobilized on silica support to form tin porphyrin-based heterogeneous sensitizer, SnP/silica.…”
Section: Preparation Of Sensitizers As Water-soluble and Immobilized mentioning
confidence: 99%
“…High-valent Sn(IV) incorporated into the porphyrin center enables electron transfer from organic substrates to 3 SnP * [31], providing an alternative reaction route for photocatalytic oxidative degradation. Our previous study [26] showed that visible light irradiation of SnP/silica led to rapid degradation of neutral phenolic compounds that are not susceptible to singlet oxygenation by aminoC 60 /silica.…”
Section: Photo-induced Electron Transfermentioning
confidence: 99%
“…Visible light photocatalysis using SiO 2 immobilized water-soluble and -insoluble tin porphyrins degraded 4-chlorophenol and Acid Orange 7 in water. Interestingly, the visible light activity of the porphyrin photocatalyst was enhanced by increasing the loading of insoluble tin porphyrin (Kim et al 2008). Photocatalysts prepared in situ by CuPc immobilization on Al and encapsulated inside zeolite-X showed a remarkable affinity towards CN − .…”
Section: Tetrapyrrole-based Photocatalystsmentioning
confidence: 99%
“…A similar carrier covalently modified with the metal-free monopyridyltriphenylporphyrin, introduced into a polymer microchannel and the microchip were applied for photodecomposition of phenol under solution-flow conditions (Kitamura et al, 2006). Very recently a visible light photocatalytical system based on waterinsoluble tin porphyrin Sn(OH) 2 (TPP) immobilized on SiO 2 has been successfully used for the degradation of 4-chlorophenol and acid orange 7 (Kim et al, 2008). Silica microspheres functionalized with 5-(4-allyloxy)phenyl-10,15,20-tri(2,6-dichlorophenyl)porphyrin have been prepared by Huang et al for the photooxidation of 1,5-dihydroxynaphthalene under visible light irradiation in the aerated aqueous solution (Cai et al, 2009).…”
Section: Photocatalytic Oxygenation Using Porphyrins Intercalated In mentioning
confidence: 99%